A Zinc–Bromine Battery with Deep Eutectic Electrolytes (Adv. Sci. 36/2022). Issue 36 (29th December 2022) - Heo, Jiyun; Shin, Kyungjae; Kim, Hee‐Tak
Abstract : Zinc–Bromine Batteries In article number 2204908, Jiyun Heo, Kyungjae Shin, and Hee‐Tak Kim demonstrate a gas‐free Zn‐Br battery by using a specifically designed deep eutectic solvent as its electrolyte. Modulating the ionic characteristics of the electrolyte by altering the halogen chemistry effectively enhances the performance of the Zn‐Br battery. Encouraged by the mitigated gas‐related issue, the Zn‐Br battery is prepared in various configurations including a flexible pouch‐type cell.